Globalization, Islam, and the West: Between Homogenization and Hegemonization (American Journal of Islam and Society, 1998)
Let us begin with the challenge of a definition. What is globulizution?It consists of processes that lead toward global interdependence and theincreasing rapidity of exchange across vast distances. The word globulizutionis itself quite new, but the actual processes toward global interdependenceand exchange started centuries ago.Four forces have been major engines of globalization across time:religion, technology, economy, and empire. These have not necessarilyacted separately, but often have reinforced each other. For example, theglobalization of Christianity started with the conversion of EmperorConstantine I of Rome in 3 13. The religious conversion of an emperorstarted the process under which Christianity became the dominant religionnot only of Europe but also of many other societies thousands ofmiles distant from where the religion started. The globalization of Islambegan not with converting a ready-made empire, but with building anempire almost from scratch. The Umayyads and Abbasids put togetherbits of other people’s empires (e.g., former Byzantine Egypt and formerZoroastrian Persia) and created a whole new civilization.Voyages of exploration were another major stage in the process ofglobalization. Vasco da Gama and Christopher Columbus opened up a ...